Students’ Perception on The Use of Movie Clips at Cake Application toIncrease Vocabulary - Wanda Anastania; Syafrizal, Syafrizal; J Pahamzah (Pencerah, 2024)
This research was intended to determine students’ perceptions on the use of Cake application in learning vocabulary. Specifically, there are two objectives of the research: 1). To find students' perceptions on the use of movie clips at Cake application to increase student vocabulary, 2). The advantages and disadvantages in learning English using movie clips at Cake application. This research used qualitative descriptive method. The participant of the research is students of the tenth-grade at SMA Islam Al-Azhar 6 Cilegon. To collect the data, this study used an open-ended questionnaire. The finding concluded two items. First, students’ perceptions on the use of movie clips at Cake application to increase student vocabulary. The results showed that students had positive perception regarding the use of movie clips at Cake application to increase student’s vocabulary. From students’ point of view, students agree that the use of movie clips feature at Cake application is really helps them in learning vocabulary, because learning to use this feature will be more fun, easier to understand and suitable for beginners. Second, the advantages of the movie clips at Cake application are the material that is very easy to learn and easy to remember because the movie clip is repeated many times so that students can memorize it more easily. The disadvantage is some respondents think that this feature duration of the movie clips provided is too short, and others said that there are no disadvantages to this feature.